2017
DOI: 10.1016/j.jmu.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

A 7-Year-Old Girl with Early Developed Pseudocyst After Acute Pancreatitis: A Case Report and Literature Review

Abstract: We report a 7-year-old Taiwanese girl with acute pancreatitis (AP) complicated with pseudocyst (PC). The girl was found to have a PC by ultrasonograpgy (USG) and magnetic resonance imaging 14 days after the onset of AP. The girl was discharged 21 days after management with an asymptomatic PC. The diagnostic criteria of AP included abdominal pain, serum amylase or lipase level, and imaging findings. Transabdominal USG after appropriate preparation with adequate fasting, intake of some liquids during the scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…CRP, TNF-α, IL-6, IL-β and surgical methods were independent risk factors for the prognosis of patients with SAP and PP. Some studies have also reported that different surgical methods directly affect the prognosis of patients (25)(26)(27). A recent study has confirmed that the prognosis of patients with SAP also needs long-term monitoring of serum inflammatory factors (28).…”
Section: Discussionmentioning
confidence: 99%
“…CRP, TNF-α, IL-6, IL-β and surgical methods were independent risk factors for the prognosis of patients with SAP and PP. Some studies have also reported that different surgical methods directly affect the prognosis of patients (25)(26)(27). A recent study has confirmed that the prognosis of patients with SAP also needs long-term monitoring of serum inflammatory factors (28).…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal ultrasound can help characterize the lesion if itis not large. Good preparation before the examination with a fasting patient from 6 to 8 hours (3 hours for newborns) combined with administration of liquid in the stomach during the examination would improve the sensitivity of the ultrasound in the supine or right lateral position ( 9 ). When the pseudocyst is bulky, an abdominal CT scan is indicated to better describe its relations, the associated signs as well as the complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the CT scan is irradiating and limited in the analysis of the contents of the pseudocyst and possible communication with the pancreatic ducts. Thus, biliopancreatic magnetic resonance imaging could be useful to unmask the communication of the pseudocyst with the pancreatic ducts and to discern necrotic debris or hematic components in the pseudocyst ( 5 , 9 ). The differential diagnosis can however be discussed between a mesenteric cyst or a digestive duplication in this localization in these pediatric populations ( 2 ) but the clinical context with the history of abdominal trauma as well as the pancreatic relations of the mass associated, in our case, with the dilation of the main pancreatic duct allow to evoke the diagnosis before the anatomopathological confirmation.…”
Section: Discussionmentioning
confidence: 99%